Bone fracture is associated with incident myocardial infarction in long-term follow-up - Mei-Liang Zheng; Xiang-Peng Du; Xin-Chun Yang; Mei-Li Zheng (BMC, 2024)
Abstract Background The association between bone fracture and cardiovascular diseases is examined in this study. While basic research has established a connection between fractures and heart attacks through the linkage between bones and arteries, population studies have not provided clear evidence. The aim of the present study is to investigate the association between bone fracture and the occurrence of myocardial infarction in a natural population during long-term follow-up. Methods A total of 13,196 adult participants with bone fracture history at baseline from the China Health and Nutrition Survey (CHNS) prospective cohort were included in this study. Baseline investigation was performed in 1997-2009 and the outcome was followed up till 2015. Hazard ratios (HRs) and their corresponding 95% confidence intervals (CIs) were calculated using Cox proportional hazards models. Results From 1997 to 2015, a total of 329 incident myocardial infarction cases were identified. In univariate and multivariate Cox regression analysis, a history of bone fracture was associated with an increased risk of myocardial infarction incidence in the total population (for the crude model: HR = 2.56, 95% CI 1.83-3.53, P < 0.001; for the multivariate model: HR = 1.43, 95% CI 1.02-1.99, P = 0.036). In the stratified analysis, bone fracture was not associated with an increased risk of incident myocardial infarction in subjects with age < 50 years (HR = 0.71, 95% CI 0.34-1.47, P = 0.356), but significantly associated with an increased risk of incident myocardial infarction in subjects with age ≥ 50 years (HR = 1.80, 95% CI 1.23-2.63, P = 0.003). Conclusions It is suggested by the present study that bone fracture may be associated with an increased risk of incident myocardial infarction in the elderly population during long-term follow-up.